Osteosynthesis in intercondylar and femoral epiphysis fracture in dog: Description of a clinical case - Angarita C., Yadira (2020)
The initial radiographic study revealed lesions that were suggestive of a fracture of the distal epiphysis of the femur and the intercondylar region. Due to the damage and compromise of the knee, it was decided to perform the arthrodesis technique with a compression plate fusing the femur and tibia. For the arthrodesis technique, a 2.7 mm compression plate with three 18 mm and one 14 mm screws placed in the proximal part and four 18 mm screws in the distal part were used. The synthesis of the internal surgical plane was performed with vicryl 1.0 and the external one with nylon. The anaesthetic procedure was routine, analgesic and antimicrobial therapy was performed with tramadol, doxycycline and metronidazole. A follow-up was performed 60 days after the intervention in which the patient showed no negative reactions. Limb mobility was successfully reduced.